(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article we have described the role of ancient turkish beliefs in kazakh nation’s worldview, and features of turkish beliefs formation and principles, history of it’s birth on kazakh territory. The concept of tengri deeply was investigated and submitted opinions of various scientists to the reader’s attention. Along with that, we have expounded about the role of tengrinism in kazakh nation’s history and in the present lifestyle. Also, deeply was discussed about elements and customs of tengrinism, were submitted complete assessment of them. It was described about connection of the history of Kazakh customs and traditions which remained as national customs and belief of tengrinism. We tried to tell more about belief of tengrinism, it’s importance and role for nomad people, and about role of harmony with nature for population of step. Key words: Turkish worldview, tengri, tengrinism, earth-water, Umai, Kut, aruak, spirit, Kazakh’s belief.